Change in Cardiopulmonary Resuscitation Performance Over Time During Simulated Pediatric Cardiac Arrest and the Effect of Just-in-Time Training and Feedback. Issue 3 (11th March 2021) - Duff, Jonathan P.; Bhanji, Farhan; Lin, Yiqun; Overly, Frank; Brown, Linda L.; Bragg, E. Alexis; Kessler, David; Tofil, Nancy M.; Bank, Ilana; Hunt, Elizabeth A.; Nadkarni, Vinay; Cheng, Adam; et al.
Abstract : Objectives: Effective cardiopulmonary resuscitation (CPR) is critical to ensure optimal outcomes from cardiac arrest, yet trained health care providers consistently struggle to provide guideline-compliant CPR. Rescuer fatigue can impact chest compression (CC) quality during a cardiac arrest event, although it is unknown if visual feedback or just-in-time training influences change of CC quality over time. In this study, we attempt to describe the changes in CC quality over a 12-minute simulated resuscitation and examine the influence of just-in-time training and visual feedback on CC quality over time. Methods: We conducted secondary analysis of data collected from the CPRCARES study, a multicenter randomized trial in which CPR-certified health care providers from 10 different pediatric tertiary care centers were randomized to receive visual feedback, just-in-time CPR training, or no intervention. They participated in a simulated cardiac arrest scenario with 2 team members providing CCs. We compared the quality of CCs delivered (depth and rate) at the beginning (0–4 minutes), middle (4–8 minutes), and end (8–12 minutes) of the resuscitation. Results: There was no significant change in depth over the 3 time intervals in any of the arms. There was a significant increase in rate (128 to 133 CC/min) in the no intervention arm over the scenario duration ( P < 0.05). Conclusions: There was no significant drop in CC depth over a 12-minute cardiac arrest scenario with 2 team members providing compressions.